Shockwave Therapy: Still Little Known Issues - Fizzotti, Gabriella; Piccinini, Maurizio; Ramella, Valeria; Fassina, Lorenzo (British Journal of Healthcare and Medical Research, 2023)
Background: In the last few years the development of Extracorporeal shock wave therapy (ESWT) was very fast. Shock waves can help reduce inflammation in muscoloskeletal areas of the body. At the first time medical ESWT was used in urologic discipline for lithotripsy therapy later the opportunity of transmit mechanical energy by shock waves led to different technical and medical applications. Aim: to evaluate the different indications for ESWT in more or less frequent orthopedic pathologies. Material and Method: We enrolled 423 patients: 174 males and 249 females. All people presented orthopedic disease with specific therapeutic indication to ESWT in skeletal segments. Conclusion: The therapeutic efficacy of ESWT is still unclear for less frequent orthopedic pathologies. Further studies needed to improve the quality of the health care preventing chronic painful disease.